The African philosophy reader : a text with readings - Coetzee, P. H. (Pieter Hendrik), 1949-; Roux, A. P. J. (New York : Routledge, 2003)
Divided into eight sections, each with introductory essays, the selections offer rich and detailed insights into a diverse multinational philosophical landscape. Revealed in this pathbreaking work is the way in which traditional philosophical issues related to ethics, metaphysics, and epistemology, for instance, take on specific forms in Africa's postcolonial struggles. Much of its moral, political, and social philosophy is concerned with the turbulent processes of embracing modern identities while protecting ancient cultures.
Some African cultural concepts / S. Biko -- Are there cultural universals? / K. Wiredu -- Ubuntu culture and participatory management / E.D. Prinsloo -- What is African philosophy? / D.N. Kaphagawani -- Sage philosophy / H.O. Oruku -- Ethnophilosophy and its critics / K.A. Appiah -- Ènìyàn: the Yoruba concept of a person / S. Ghadegesin -- African conceptions of personhood and intellectual identities / D.N. Kaphagawani -- The concept of cause in African thought / G.S. Sogolo -- On decolonizing African religions / K. Wiredu -- Logic and rationality / G.S. Sogolo -- The concept of truth in the Akan language / K. Wiredu -- Themes in a Chewa epistemology / D.N. Kaphagawani -- Old Gods, new worlds / K.A. Appiah -- Individuality, community, and the moral order / S. Ghadegesin -- The moral foundations of an African culture / K. Wiredu -- Person and community in African thought / K. Gyekye -- The definition of Black consciousness / S. Biko -- Outlawing racism in philosophy: on race and philosophy / M.P. More -- Democracy and consensus in African traditional politics: a plea for a non-party polity / K. Wiredu -- Traditional African aesthetics: a philosophical perspective / I.C. Onyewuenyi -- Morality, art, and African philosophy: a response to Wiredu / P. English & N. Steele-Hamme -- Is primitive art "art"? / G. Blocker -- On the distinction between modern and traditional African aesthetics / G. Blocker -- Negritude and African socialism / L.S. Senghor.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Philosophy, African; Philosophie africaine; PHILOSOPHY -- History & Surveys -- Modern; Philosophy, African